Influencia de las regalías en el desarrollo local de los municipios de Castilla la Nueva y Puerto Gaitán del departamento del Meta (2010-2017) (2020)
The first part of this document, the main theories based on local development, measured by population needs, as well as the laws that support royalties and additionally, are defined fundamental concepts such as: Royalties and local development. Secondly, a brief determination of the FNR is made and after this, a description of the SGR is made, as well as the organs that compose it, and the assignment it makes to the Meta department, specifically to the municipalities of Castilla La Nueva and Puerto Gaitán Finally, a comparison is made between these two schemes. In the third instance, the evolution of local development in the municipality of Castilla La Nueva and Puerto Gaitán of the department of Meta is described, where social, political, economic and technological aspects are taken into account. Finally, the relationship between the two study variables in the municipalities of Castilla la Nueva and Puerto Gaitán in the aspects mentioned above is presented, and a brief comparison is made between these two municipalities.